Draft Regulatory Reform Bill, 20** - Planning Commission (Planning Commission, 2009)
After a series of wide ranging consultations with experts and stakeholders, the Government published a paper titled “Approach to Regulation of Infrastructure”. It analyses the current slate of economic regulation and suggests an overarching framework with a view to addressing the divergent mandates and practices prevailing in different sectors. The Approach Paper underscores the need to establish a level playing field wherever the industry structure is amenable to competition. It recommends sound regulatory principles and practices where monopoly services are to be regulated. The Approach Paper identifies some general principles which are critical to the institutional design of regulation in the context of values enshrined in the Constitution.
Planning Commission Government of India
Planning Commission Government of India